Penilaian Investasi Teknologi Informasi STMIK Indonesia Padang Menggunakan Val IT Framework 2.0 Domain Investment Management (IM) - Gusman, Anisya; Winarno, Wing Wahyu; Nasiri, Asro (The Indonesian Journal of Computer Science, 2022)
IT investment is an investment that can be made to increase resources from IT expenses by utilizing these expenditures to achieve the expected value. In measuring IT values in a business context, one methodology that can be used is Val IT. Val IT has three domains, one of which is Investment Management (IM). The results obtained at STMIK Indonesia Padang in developing and evaluating the concept of business case programs are still at level 2 where this means the campus has built a business case but is still unclear. But overall, STMIK Indonesia Padang is at level 3 where this is at the defined level so that STMIK Indonesia Padang is increasingly aware of the importance of managing changes and procedures carried out have been passed, documented and communicated. But at the implementation stage it is still individual.